Religious Education Counseling in Religious Rehabilitation for Child Victims of Sexual Abuse( A Case Study at the Women’s Empowerment, Child Protection, Population Control, and Family Planning Service of Sambas Regency) - Ria Rachmawati; Arnadi Arnadi; Nuraini Nuraini (International Journal of Education and Literature, 2025)
This research is motivated by the increasing number of cases of child sexual abuse that cause serious psychological impacts in the form of trauma and emotional development disorders. The purpose of this study is to describe and analyze the process of religious guidance through Islamic religious education counseling for child victims of sexual abuse, which includes four main aspects, namely: (1) planning religious guidance, (2) implementing religious guidance activities, (3) strengthening religious guidance, and (4) supervision in the guidance process. This study uses a qualitative method with data collection techniques through interviews, observations, and documentation. The validity of the data is tested using triangulation and member check techniques. The results of the study indicate that religious guidance planning is carried out by compiling programs, scheduling activities, and evaluating the results of guidance. The implementation of activities is carried out through religious counseling, psychological approaches, and integration of spiritual values to help children understand and internalize religious teachings independently. Strengthening guidance is carried out through spiritual counseling services, psychological assistance, and legal assistance for victims. Meanwhile, supervision of guidance is carried out through optimizing the role of the community in community-based child protection groups as an integrated system to create a safe and child-friendly environment.